Comprehensive Analysis of Treatment Approaches in Chest Wall Ewing Sarcoma: The Impact of Tumor Volume on Oncologic Outcomes - Brady S. Laughlin, MD; Aaron Bogan, MA; Wendy A. Allen-Rhoades, MD, PhD; Peter S. Rose, MD; Stephanie F. Polites, MD, MPH; Jonathan B. Ashman, MD, PhD; Ivy Petersen, MD; Michael G. Haddock, MD; Anita Mahajan, MD; Nadia N. Laack, MD; Safia K. Ahmed, MD (Advances in Radiation Oncology)
Purpose: Local treatment with surgery (S) and radiation therapy (RT) for chest wall Ewing sarcoma (cwES) is often challenging given the extent of the tumor and the aggressiveness of local treatments needed for cure. We report tumor and treatment characteristics, oncologic outcomes, and toxicities of patients with cwES at 2 centers of a single institution. Methods and Materials: Consecutive patients with cwES treated from 1997 to 2022 were retrospectively reviewed. All patients were treated with standard 5-drug chemotherapy (vincristine, doxorubicin, cyclophosphamide, alternating with ifosfamide and etoposide) before initiation of local therapy. Local treatment was S, RT, or both. The decision on modality and timing was determined by a multidisciplinary sarcoma group or by consensus between sarcoma experts regarding patient preferences. Results: The cohort consisted of 39 patients. The median age at diagnosis was 19.2 years (range, 3.5-53.6 years). Median tumor volume (TV) was 235.5 mL (range, 5.3-6761.9 mL). The local control (LC) modality was S in 18 patients (46%), RT in 4 (10%), and S + RT in 17 (44%). Four (10%) patients treated with S + RT had R1 margins. The median follow-up was 3.2 years (range, 0.1-21.6 years). Grade 3 radiation-associated toxicity relative to the RT modality was 16.7% and 7.1% for photons (n = 6) and protons (n = 14), respectively. The 2-year LC by modality was 100% for RT (95% CI, 100%-100%), 88.2% (95% CI, 74.2%-100%) for S, and 73.3% (95% CI, 54.0%-99.5%) for S + RT. The 5-year LC, failure-free survival, and overall survival for all patients were 79.7% (95% CI, 67.3%-94.4%), 52.3% (95% CI, 38.1%-71.9%), and 64.2% (95% CI, 49.6%-83.1%), respectively. In univariate and multivariate analysis, TV ≥ 130 mL was associated with a significantly worse 5-year failure-free survival (31.8% TV ≥ 130 mL vs 80.8% TV < 130 mL; hazard ratio, 4.94, p = .013 and adjusted hazard ratio, 5.43; 95% CI, 1.28-22.98; p = .022). The multivariate model was adjusted for age, metastatic disease at diagnosis, and S. Conclusions: Outcomes for cwES tumors are highly dependent on tumor size, even with the use of combined modality local therapy. With early follow-up, smaller tumors may be well controlled with either S or RT.